2020
DOI: 10.3390/ani10122199
|View full text |Cite
|
Sign up to set email alerts
|

State-of-the-Art of the Nutritional Alternatives to the Use of Antibiotics in Humans and Monogastric Animals

Abstract: In recent years, the indiscriminate use of antibiotics has been perpetrated across human medicine, animals destined for zootechnical productions and companion animals. Apart from increasing the resistance rate of numerous microorganisms and generating multi-drug resistance (MDR), the nonrational administration of antibiotics causes sudden changes in the structure of the intestinal microbiota such as dysbiotic phenomena that can have a great clinical significance for both humans and animals. The aim of this rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 253 publications
1
16
0
Order By: Relevance
“…The lack of growth response attributable to AGP was unexpected since, for several decades, it was one of the main feeding alternatives in the control of post- Alam et al (2014) considered antibiotics as an additive that inherently causes dysbiosis, an imbalance in the number and composition of commensal intestinal bacteria, which eventually did not occur in piglets in the control group or those that consumed 30 mg of IAP. Study reports also showed that treatment with tiamulin as an AGP triggered intestinal dysbiosis (Le Roy et al 2019;Saettone et al 2020). These results are supported by the explanations that IAP added at 30 mg acted as a host defence factor (Koyama et al 2002), but a better understanding of the factors that regulate IAP expression and its effects on the promotion of intestinal health is needed, consequently, it improves the growth performance of piglets.…”
Section: Growth Performance Testing and Diarrhoea Incidencementioning
confidence: 90%
“…The lack of growth response attributable to AGP was unexpected since, for several decades, it was one of the main feeding alternatives in the control of post- Alam et al (2014) considered antibiotics as an additive that inherently causes dysbiosis, an imbalance in the number and composition of commensal intestinal bacteria, which eventually did not occur in piglets in the control group or those that consumed 30 mg of IAP. Study reports also showed that treatment with tiamulin as an AGP triggered intestinal dysbiosis (Le Roy et al 2019;Saettone et al 2020). These results are supported by the explanations that IAP added at 30 mg acted as a host defence factor (Koyama et al 2002), but a better understanding of the factors that regulate IAP expression and its effects on the promotion of intestinal health is needed, consequently, it improves the growth performance of piglets.…”
Section: Growth Performance Testing and Diarrhoea Incidencementioning
confidence: 90%
“…For all of these reasons, the choice of probiotics (e.g., Lactobacilli spp. and Bifidobacteria), prebiotics (e.g., fructooligosaccharides and galactooligosaccharides), and antioxidants (e.g., vitamin E, carotenoids, lutein, vegetable oil) has increased in both human and veterinary medicine [18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Postbiotics consist of a wide range of effector molecules [ 10 ] and they are capable of reducing the gut pH and, in turn, inhibiting the proliferation of opportunistic pathogens in the feed and gut microbiota [ 10 , 11 ]. Postbiotics, especially those derived from metabolites of Lactobacillus , have been proposed as an alternative to the use of antibiotics, not only in humans, but also in monogastrics [ 12 ]. Currently, the application of postbiotics in human food, animal feed and pharmaceutical industries is increasing and postbiotic products derived from Lactobacillus species are commercially available for prevention or treatment of some diseases [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the productivity, welfare and health of males should be improved by handling or feeding. Unlike other monogastric animals, data on the use of postbiotics in rabbits are quite scarce [ 12 ]. The aim of this study is to study the effect of supplementation with a postbiotic based on lactic acid bacteria on semen characteristics and hematological and biochemical profiles in male rabbits.…”
Section: Introductionmentioning
confidence: 99%